Influence of homestay, socio-economic status and computer literacy on undergraduates’ learning attitude during COVID-19 pandemic in the university of Ibadan (2022)
It is widely known that formal learning is best experienced in the confinement of classroom environment. Educational and other related activities were mopped together because of homestay induced by COVID-19 pandemic, resulting in remote teaching-learning mode and manipulations of computers and the internet which were alien to some undergraduates and lecturers. The study therefore, examined the influence of Homestay, Socio-Economic Status and Computer Literacy on Undergraduates' Learning Attitude during Covid-19 Pandemic's Induced “Pedagogical Restructuring’’ in the University of Ibadan. Ex-post facto design ofcross-sectional study and multi-stage sampling techniques guided the study. Five faculties, 20 departments, 30 Economics, 400 undergraduates and 30 teachers were randomly selected for the study. Three research questions and three validated instruments-Depression, Anxiety and Stress Scales (r = 0.85), Undergraduates' SocioEconomic Status and Computer Literacy Scale (r = 0.75), Attitude to Learning Scale (r = 0.70), were used in the study. Data obtained were analysed using descriptive statistics and multiple regression at 0.05. Results revealed that most respondents experienced one psychological trauma during COVID-19 pandemic homestay. Further finding showed that independent variables were reliable predictors of undergraduates' attitude to learning during COVID-19 pandemic homestay (F(2.396) =9.470, p<0.005). Computer literacy made the highest contribution to the students' attitude to learning (β = 1.91, t = 3.815, p<0.05), followed by experiences of the undergraduates (β = .159, t = 3.174, p<0.05). The paper recommends that the University of Ibadan management should consider the socio-economic status of its undergraduates before advancing into individual differences', sensitive educational event such as adoption of online platforms during COVID-19 pandemic.